Sosialisasi Cara Produksi Pangan Olahan yang Baik (CPPOB) Produk Olahan Mangrove - Anita Suri; Supriyanto Supriyanto; Andini Riandi; Herol Herol; Ade Rukmansyah (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
Muara Gembong is one of the sub-districts in Bekasi Regency. Pantai Bahagia Village is a coastal village with a mangrove ecosystem. The abundance of mangrove fruits and leaves is used by Kebaya MSMEs as processed food products. People are increasingly smart in choosing safe, healthy and nutritious products so that mangrove processed products need to make improvements at every stage of the processing process. Socialization of good processed food production methods (CPPOB) for mangrove processed products will be carried out directly at the Kebaya MSME Production House in August 2023. This socialization activity was attended by 26 participants. Analysis of production sites carried out eight aspects, namely: Environmental aspects of production; buildings and facilities; production equipment; hygiene and sanitation facilities; Employee health and hygiene, process control, food labeling, record keeping and documentation. The results of the discussion of Kebaya MSMEs will be committed to making improvements in implementing CPPOB in every production activity in accordance with established standards.